1985
DOI: 10.1055/s-0038-1657748
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of β2-Glycoprotein-I with Human Blood Platelets: Influence Upon the ADP-Induced Aggregation

Abstract: SummaryThe interaction of β2-glycoprotein-I (β2-G-I), a plasma constituent of unknown function, with blood platelets was studied. The following results were obtained: 1) β2-G-I binds to washed human platelets isolated by centrifugation (WP) at one kind of specific, saturable binding sites. The dissociation constant was found to be approx. 1 × 10−6M.2) In the presence of physiological concentrations of Ca++ (2.5 mM), this specific binding is markedly reduced. Unspecific binding of β2-G-I to platelets, however, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
65
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 24 publications
0
65
0
Order By: Relevance
“…Limited analysis of such individuals has shown that they are not prone to thrombosis (20,21). Beta 2 -glycoprotein I has anticoagulant properties since it can inhibit ADPmediated platelet aggregation (22) and the activation of FXI by thrombin and FXIIa (23). On the other hand, ␤ 2 GPI impairs activated protein C, suggesting that it may also serve a procoagulant function (24).…”
mentioning
confidence: 99%
“…Limited analysis of such individuals has shown that they are not prone to thrombosis (20,21). Beta 2 -glycoprotein I has anticoagulant properties since it can inhibit ADPmediated platelet aggregation (22) and the activation of FXI by thrombin and FXIIa (23). On the other hand, ␤ 2 GPI impairs activated protein C, suggesting that it may also serve a procoagulant function (24).…”
mentioning
confidence: 99%
“…P,-GPI consists of 326 amino acids and binds to anionic PLs (14,1&21). This molecule has been reported to inhibit ADP-induced aggregation of platelets, activation of the intrinsic coagulation pathway, and prothrombinase activity of platelets (22)(23)(24). Anticardiolipin antibodies may affect some of these antithrombotic functions of P,-GPI and induce hypercoagulability and thrombosis.…”
mentioning
confidence: 99%
“…β2GPI, also known as apolipoprotein H, is a 50-kDa phospholipid-binding protein present in plasma at an approximate concentration of 200µg/ml, and has been recognized as a natural anti-coagulant because β2GPI inhibits prothrombinase and tenase function, factor XII activation and ADP-dependent activation of platelets (Nimpf et al, 1986;Schousboe et al, 1995;Nimpf et al, 1985). Recently, β2GPI has been shown to bind directly to factor XI and attenuate its activation (Shi et al, 2004).…”
Section: Impaired Fibrinolysismentioning
confidence: 99%